Trojan horses: Creating a positive hidden (extra)curriculum through a Justice, Equality, Diversity and Inclusion (JEDI) initiative. Issue 3 (July 2023) - Keshtiban, Amir; Gatto, Mark; Callahan, Jamie L
In this paper, we describe a mechanism for subverting the institutional-level neo-liberal hidden curricula of responsibility learning in universities by using a positive hidden curriculum based on extra-curricular activities partnering staff and students. In our study, we leverage projects from an institution-sponsored Justice, Equality, Diversity and Inclusion (JEDI) initiative as notional 'Trojan horses' to instil within university students a more reflexive awareness of responsibility that they can take with them when they graduate. In delivering this positive hidden (extra)curriculum, staff are seemingly performing the formal agenda of the institution's responsibility agenda while undermining its managerialist hidden curriculum by working in tandem with students. Our key findings – student reflection and voice – are evidence of the positive hidden curriculum implementation. Our contributions are twofold. First, we demonstrate that positive hidden curricula can serve as a tool of micro-activism to subvert managerialist hidden curricula. Second, we offer another dimension to Semper and Blasco's interpersonal strategies for challenging the hidden curriculum by showing that collaborative projects between students and staff can be sites of a positive hidden (extra)curriculum. Collaborative initiatives such as the ones we describe in this article provide a tangible foundation for reconsidering creative and intrinsic approaches to responsible learning environments.